Investigating the functional neuroanatomy of concrete and abstract word processing through direct electric stimulation (DES) during awake surgery. Issue 3 (19th May 2019) - Orena, E. F.; Caldiroli, D.; Acerbi, F.; Barazzetta, I.; Papagno, C.
ABSTRACT: Neuropsychological, neuroimaging and electrophysiological studies demonstrate that abstract and concrete word processing relies not only on the activity of a common bilateral network but also on dedicated networks. The neuropsychological literature has shown that a selective sparing of abstract relative to concrete words can be documented in lesions of the left anterior temporal regions. We investigated concrete and abstract word processing in 10 patients undergoing direct electrical stimulation (DES) for brain mapping during awake surgery in the left hemisphere. A lexical decision and a concreteness judgment task were added to the neuropsychological assessment during intra-operative monitoring. On the concreteness judgment, DES delivered over the inferior frontal gyrus significantly decreased abstract word accuracy while accuracy for concrete words decreased when the anterior temporal cortex was stimulated. These results are consistent with a lexical–semantic model that distinguishes between concrete and abstract words related to different neural substrates in the left hemisphere.